2000
DOI: 10.1074/jbc.m000942200
|View full text |Cite
|
Sign up to set email alerts
|

The Noncatalytic β-Propeller Domain of Prolyl Oligopeptidase Enhances the Catalytic Capability of the Peptidase Domain

Abstract: Prolyl oligopeptidase, which is involved in memory disorders, is a member of a new family of serine peptidases. In addition to the peptidase domain, the enzyme contains a beta-propeller, which excludes large peptides from the active site. The enzyme is inhibited with thiol reagents, possibly by reacting with Cys-255 located close to the substrate binding site. This assumption was tested with the Cys-255 --> Thr, Cys-255 --> Ala, and Cys-255 --> Ser variants of prolyl oligopeptidase. In contrast to the wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Unlike the sigmoid or bell-shaped pH rate profiles observed with the classic serine peptidases, the pH dependence for prolyl oligopeptidase is more complicated. This has previously been shown with Z-Gly-Pro-Nap (24,25) and also demonstrated here with the octapeptide substrate. As seen in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Unlike the sigmoid or bell-shaped pH rate profiles observed with the classic serine peptidases, the pH dependence for prolyl oligopeptidase is more complicated. This has previously been shown with Z-Gly-Pro-Nap (24,25) and also demonstrated here with the octapeptide substrate. As seen in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Unlike the sigmoid or bell-shaped pHrate profiles observed with the classic serine peptidases, the pH dependence for prolyl oligopeptidase is more complicated. This has been shown with several substrates [60,62,63]. As seen in figure 3A, the data conform to a doubly bell shaped curve, which arises from modification of the usual bell-shaped curve by an additional ionization event involving a group with an apparent pK a of ~7.…”
Section: Kinetic Propertiesmentioning
confidence: 66%
“…In contrast, the loop A (T202C) and loop B (T590C) point mutants displayed altered ligand binding but relatively unaltered catalytic activity. Different again, in previous studies the Asp loop (D641A) and the Cys loop (C255A) variants showed altered pH dependencies, but ligand binding was only slightly affected [40,43]. This implies a much greater corruption of the active site structure in the loop A -variant.…”
Section: Crystal Structure Of the H680a Variant Reveals Cooperation Bmentioning
confidence: 87%
“…The further change in the preference for ZGly-Pro-BNA over the longer octapeptide upon air and glutathione oxidation is presented in Table 2. The oxidized glutathione partially inactivated (30%) the wild-type POP too, but equally for both the shorter and the longer peptide, while the C255S control variant not containing the C255 responsible for the thiol-sensitivity of POP activity [40] retained the initial activity. 89 % and 87% of the activity of the glutathione-oxidized and air-oxidized T202C/T590C variant could be recovered with a DTT treatment (10 mM), respectively.…”
Section: A Chemical Cross-link Between Loop a And Loop B Inactivates mentioning
confidence: 99%